2009
DOI: 10.1097/chi.0b013e31819f70fb
|View full text |Cite
|
Sign up to set email alerts
|

Startle Response in Behaviorally Inhibited Adolescents With a Lifetime Occurrence of Anxiety Disorders

Abstract: Objective Behaviorally inhibited children face increased risk for anxiety disorders, although factors that predict which children develop a disorder remain poorly specified. The current study examines whether the startle reflex response may be used to differentiate between behaviorally inhibited adolescents with and without a history of anxiety. Method Participants were assessed for behavioral inhibition during toddlerhood and early childhood. They returned to the laboratory as adolescents and completed a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 37 publications
9
62
0
Order By: Relevance
“…This lack of specificity in the implementation of both automatic and control processes limits the flexibility and efficiency of information processing. This model is consistent with findings that children with a history of early BI show exaggerated startle responses to safety cues (Barker et al, 2014) and that adolescents with a history of childhood BI and also a lifetime diagnosis of anxiety show the same pattern of startle reactivity to safety cues (Reeb-Sutherland et al, 2009a). This is also consistent with the Perez-Edgar et al (2007) finding that adolescents with a history of childhood BI showed exaggerated amygdala responses to all emotion faces (not just threatening ones) when asked to rate their subjective experiences.…”
Section: Overgeneralized Control Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…This lack of specificity in the implementation of both automatic and control processes limits the flexibility and efficiency of information processing. This model is consistent with findings that children with a history of early BI show exaggerated startle responses to safety cues (Barker et al, 2014) and that adolescents with a history of childhood BI and also a lifetime diagnosis of anxiety show the same pattern of startle reactivity to safety cues (Reeb-Sutherland et al, 2009a). This is also consistent with the Perez-Edgar et al (2007) finding that adolescents with a history of childhood BI showed exaggerated amygdala responses to all emotion faces (not just threatening ones) when asked to rate their subjective experiences.…”
Section: Overgeneralized Control Modelsupporting
confidence: 78%
“…This study found that hypersensitivity to novelty significantly increased risk for anxiety diagnoses but only among adolescents with a childhood history of BI. Similar findings emerged in a second report from Reeb-Sutherland et al (2009a), where risk moderation was indexed by enhanced startle response, not to threat, but to safety cues. Finally, three studies used the dot-probe task to demonstrate similar patterns of risk moderation by automatic modes of processing.…”
Section: Risk Moderationsupporting
confidence: 69%
“…[83] For example, anxiety disorders are characterized by various specific biases in attention to threat and in startle response. [83,92,93] In contrast, OCD may be particularly strongly characterized by thought-action fusion, or the belief that thinking about an unacceptable event makes that event more probable, leading to an inflated sense of responsibility, although not all data are consistent. [94] Table 1 summarizes the profile of cognitive deficits across individual anxiety disorders.…”
Section: This Issue)mentioning
confidence: 85%
“…Background anxiety is likely an important dimension of anxiety that is expressed in many mental health disorders. PTSD, panic disorder, and autism spectrum subjects, behaviorally inhibited adolescents, and people going through nicotine withdrawal display enhanced startle during unpredictable threat, but still have normal cued-fear-potentiated startle (Bernier et al, 2005;Brunetti et al, 2010;Dichter et al, 2010;Grillon and Morgan, 1999;Grillon et al, 1996Grillon et al, , 1998Grillon et al, , 2009Hogle et al, 2010;Morgan et al, 1995;Pole et al, 2003Pole et al, , 2009Reeb-Sutherland et al, 2009;Wilbarger et al, 2009). The disorders appear to share a clinical phenotype characterized by anxious apprehension, hypervigilance, and exaggerated responsivity during unpredictable, but not predictable, aversive events (Grillon, 2009;Rosen and Schulkin, 1998).…”
Section: Discussionmentioning
confidence: 99%